ANALISIS PENGARUH MOTIVASI TERHADAP KUALITAS PELAYANAN PUBLIK (Studi Pada Bidang Perhubungan Darat Dinas Perhubungan Kabupaten Kutai Timur) - Alam, Syamsul (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the motivation to have a positive effect on the Quality of Public Services in the Field of Land Transportation of East Kutai District Department of Transportation.The results showed that there is a positive and significant relationship between motivation variables with variable Quality of Public Services in the Field of Land Transportation of East Kutai District Department of Transportation. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.630, which means there is a strong relationship between the two variables.While the results of the t test (t-test) demonstrated that the resulting empirical t is equal to 4.077. These results are compared with the prices of the table critical t for n - 2 is 1.717. This means that there is a significant influence between the variables of motivation on the Quality of Public Services. Thus it can be said that the goal of this research can be achieved, the problems can be solved and hypotheses can be proven.